Constituency Politics and Public Policymaking: Dilemma of Development Projects in Rawalpindi District in Pakistan - Muhammad Rehman; Hina Shahid (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Policymaking involves various power structures, stakeholders, and interest groups, all of which have an individual and collective impact on policy formulation, design, and implementation. In the political context, constituency is crucial, and policy programs in democratic systems are influenced by various constituency mechanics. In the case of Pakistan, internal migration and urbanization over the last four decades coupled with population increase have changed demographics in various urban constituencies giving rise to new power structures. The problem with the political system is that, while politically motivated choices in development projects are made to ensure societal welfare, they sometimes triumph over the public policy process and serve as instruments of power entrenchment and perpetuation. This study investigates whether political parties formulate policies to win elections or to ensure societal welfare? The objective of the study is to get empirical data to unveil the underlying political machinations at work, from inception to conclusion of developmental projects, and measure the impact of such considerations on the efficacy of the immediate project. The qualitative and quantitative methods were applied to gather data and results. SPSS was used for analysis of association among variables, regression analysis and tests of significance.